Predictive factors for re-bleeding of esophageal varices in hospitalized patients: Predictive factors for re-bleeding of esophageal varices - Yaru, Han; Mei, ZuJin; Kaixin, Li; Ruyue, Chen; Mingshu, Liu (Cellular and Molecular Biology, 2022)
Bleeding due to esophageal varices is associated with high mortality and hospital costs. The incidence of morbidity and mortality can be reduced with appropriate treatment measures by identifying the predictors of re-bleeding at admission. Therefore, this study aimed to determine the risk factors for re-bleeding in hospitalized esophageal varices patients using factors included in the Child Turcotte Pugh (CTP) scoring system. In this cross-sectional study, 100 patients were evaluated for bleeding from esophageal varices. Some characteristics and variables were recorded, including age, gender, cause of disease, CTP classification score, and clinical, endoscopic, and laboratory findings. Patients were divided into two groups with and without bleeding from esophageal varices, and predictive factors were identified in both groups. Besides, a genetic predictor factor, i.e. plasminogen activator inhibitor type I (PAI-1), was evaluated by the Real-time PCR technique. Sixty-eight patients in the non-re-bleeding group with a mean age of 49.88 ± 16.42 years and 32 patients with a mean age of 54.22 ± 19.81 years were in the group with re-bleeding. Varicose vein size, encephalopathy, ascites, and CTP classification had a predictive effect on re-bleeding. Twelve people were in class A, 59 people in class B and 29 people in class C had CTP classification. The sensitivity of CTP, PAI-1 gene expression, and bilirubin in prediction through the ROC chart were calculated to be more than 85%, 61.4%, and 62%, respectively. In general, determining the degree and score of CTP at the time of referral of a patient with varicose hemorrhage provides valuable information on the risk of bleeding. Patients with class B CTP were strongly susceptible to re-bleeding in this study. Also, with increased bilirubin or ascites and more severe encephalopathy, the risk of bleeding is higher, and these people should be followed up.